Awareness and Utilization of Adolescent Sexual and Reproductive Health Services among Secondary Students - G.C., Gyanu; Thapaliya, Rekha (Journal of Biratnagar Nursing Campus, 2025)
Introduction: Adolescent sexual and reproductive health (ASRH) is a major global health concern, and neglecting it can lead to long-term negative consequences. Despite its importance, awareness and utilization of ASRH services remain low. This study aimed to assess the awareness and utilization of ASRH services among secondary school students. Methods: A descriptive cross-sectional study was conducted among adolescent students in grades 11 and 12 at Shree Krishna Sanskrit and General Secondary School, Surkhet. A complete enumeration was conducted, and data were collected from a total of 200 students using a structured self-administered questionnaire. Descriptive and inferential statistics, including the chi-square test, were used for data analysis. Results: The mean age of the respondents was 16.43±0.888 years, with among them 53.5% male and 66% living with both parents. Almost all (97.5%) were unmarried, and 66.5% lived within a 30-minute walking distance to a health facility. More than half of the respondents (65.5%) had moderate awareness of sexual and reproductive health, among them only 10.5% had used ASRH services. A large number (86.5%) did not use ASRH services because they felt they did not need them. Awareness was significantly associated with family type (p=0.001) and distance to health facilities (p=0.007). Utilization was significantly linked to sex (p=0.000) and marital status (p=0.009) Conclusion: It is concluded that the more than half of respondents had a moderate level of awareness about sexual and reproductive health, and one-tenth had utilized ASRH services within the past 12 months. Awareness-raising programs on ASRH could be implemented through schools to enhance both awareness and service utilization.